(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Although linguists have not come to a clear consensus on whether the communication environment in which speech acts occur is limited or not, their contextual function performs different tasks under the influence of factors such as time and space, the speaker’s communicative goal, and the background knowledge of the communication participants. Even one text can perform several functions depending on the context under the influence of the factors. Based on the functions of the language, speech acts in the process of communication perform various contextual tasks based on the communication goal and intention of the addressee, the content of the information being sent, and the situation in which the speech act occurs.